2011
DOI: 10.1002/pat.1978
|View full text |Cite
|
Sign up to set email alerts
|

Foaming behavior, cellular structure and physical properties of polybenzoxazine foams

Abstract: In this paper, polymer foams based on a benzoxazine resin have been successfully prepared using azodicarbonamide (ADC) as a chemical blowing agent and have been characterized regarding their foaming behavior, cellular structure, and physical properties. The effect of the ADC on the curing process of the resin was analyzed using differential scanning calorimetry and blowing agent decomposition was followed by thermogravitmetric analysis (TGA). The characterization of the cellular structure of the foamed samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Lorjai et al , prepared polybenzoxazine foams by both the sol–gel method and using azodicarbonamide as a foaming agent, and the highest compressive strength of 12.4 MPa was reached. Ardanuy et al also used azodicarbonamide as a foaming agent to prepare polybenzoxazine foams, and good mechanical strength was achieved. Zúñiga et alsynthesized benzoxazine from diphenolic acid and found that it could self-foam through decarboxylation during curing.…”
Section: Introductionmentioning
confidence: 99%
“…Lorjai et al , prepared polybenzoxazine foams by both the sol–gel method and using azodicarbonamide as a foaming agent, and the highest compressive strength of 12.4 MPa was reached. Ardanuy et al also used azodicarbonamide as a foaming agent to prepare polybenzoxazine foams, and good mechanical strength was achieved. Zúñiga et alsynthesized benzoxazine from diphenolic acid and found that it could self-foam through decarboxylation during curing.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] In addition, polybenzoxazine is compatible with various thermosetting resins and can be stored at room temperature, which makes it a potential candidate to replace phenolic resins in many fields. [20] In view of these valuable properties of polybenzoxazine and in order to address the issue mentioned above on the brittlenes of the phenolic foam, we consider that polybenzoxazine foam may be an appropriate material for polymeric foams with good mechanical and thermal properties and fire resistance. [21] However, the research of polybenzoxazine foams is far from adequate and only few reports are disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] However, the research of polybenzoxazine foams is far from adequate and only few reports are disclosed. Ardanuy et al [ 20 ] prepared and characterized polybenzoxazine foams using azodicarboxylamine (ADC) as a chemical blowing agent. The results revealed that the curing process and gas release took place in a similar time interval.…”
Section: Introductionmentioning
confidence: 99%
“…9 Research has also been conducted on high-temperature foams based on other polymers such as polysulfone, polyethersulfone, or polyetheretherketone although to our knowledge, some of these are not commercially-available at present. [10][11][12][13][14][15][16][17][18][19] All of these foams share one or more of the following key characteristics: high glass transition temperature (T g ), high melting point, chemically-stable at high temperature. In contrast to these examples of high-temperature foams, the more common foams cannot survive high temperatures because their T g is too low (e.g., polystyrene foam), melting point is too low (e.g., polyethylene foams), or they have poor chemical stability (e.g., polyurethane foams, which also often have a low melting or T g ).…”
Section: Introductionmentioning
confidence: 99%